APLIKASIPROGRAM TOPOCAD UNTUK PENGGAMBARAN HASIL UKUR TANAH - Sunar Rochmadi , Afif Nofarida (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2006)
ABSTRACTConstruction works need various drawings, including the drawings ofearth surface profiles used to prepare plan and design of construction works.If the drawing process of earth surface profile is conducted manually, it will takerelatively longer time. Using Topocad program it is hoped to produce highprecission earth surface profiles. This research aims to prove that the drawingprocess is more effective and efficient using Topocad computer program.This research was conducted using the Football Field ReplacementDevelopment Project in Dusun Kayen, Desa Sinduadi, Kecamatan Mlati,Kabupaten Sleman, Yogyakarta. The field measurement was conducted togather data used to calculate distance and height difference between points.The data were processed in the Surveying Laboratory, FaCUlty of Engineering,UN~Based on data analysis, it is concluded that the calculation process ofsurveying data is more effective and efficient supported by Microsoft Excelsoftware. Applying Topocad program using the surveying data results singlecross sections, multiple cross section, single long section, polygon and crosssection detail were drawn digitally. The drawings produced utiliZing Topocadprogram are easy to be edited and therefore should be suitable for planningand designing civil construction works, because the drawings are in theenvironment of the AutoCAD software.Key words: Earth surface~ profile, computer aided drawing, surveying drawing.